Pemanfaatan Influencer Produk Somethinc Dalam Strategi Digital Marketing di Kalangan Masyarakat - Azzahra Nasyatra Sulindra; Ariana Widya Ningsih; Ariyo Wibowo; Erwin Permana (Universitas Veteran Bangun Nusantara, 2022)
The marketing strategy using influencers is included in one of the business strategies, namely viral marketing. Viral marketing can be interpreted as a marketing strategy that is carried out by disseminating product information or opinions to the surrounding environment by word of mouth using digital media. One of the brands that utilizes digital media platforms as a strategy to market their products is Somethinc. This study aims to analyze the use of Somethinc influencer products in digital marketing strategies among the public. The research was conducted with a qualitative approach. The data was obtained from observing the digital media used by Somethinc's products. To strengthen the observation results, searches were carried out in the official media and the results of scientific publications. The results of the study show that Somethinc uses a digital marketing strategy by utilizing influencers which is done by promoting their products or commonly called endorsements. These influencers promote on their social media accounts and then swatch or try the product directly on their skin and then review it by giving positive comments about the product. Somethinc also has several Brand Ambassadors from within the country and abroad to collaborate to help promote Somethinc products to the wider community. Suggestions for writers are to examine more deeply and comprehensively about the marketing strategy for the Somethinc brand using Viral Marketing techniques through influencers and Brand Ambassadors.